Motivation, Commitments and Cultural Learning Environment of Learning Achievement TOEFL Preparation Course Participants in Central University Language Hasanuddin - Ghofar Ilmi Kristianto; Muhammad Ali; Andi Aswan (Digital Economy and Digital Transformation Review, 2023)
one of the benchmarks for pupil competence can be measured via their studying achievement, that is additionally a prerequisite for a person who desires to work in an company. gaining knowledge of performance finished by way of someone within the teaching and mastering method can have an impact on getting to know effects which can be in accordance with their performance. what is the relationship between motivation, dedication, learning surroundings way of life on overall performance? There are nevertheless few researchers who discover this question. This study aims to determine the effect of motivation, commitment, and learning environment culture on learning achievement (increase in English scores/TOEFL scores) of English course participants at the Language Center of Unhas. This research was conducted at the Hasanuddin University Language Center. The population involved 150 English language course participants (TOEFL Preparation). The number of samples in this study were 100 people from TOEFL Preparation course participants, the number of samples was obtained from the results of the Slovin formula. The sampling technique used is random sampling. Sources of data collection were English language course participants at the Unhas. Data collection techniques consist of subject analysis, observation, questionnaires and literature studies. The analysis technique used is multiple regression analysis. The results showed that all hypotheses were accepted. Based on the test that the variables of motivation, commitment and culture of the learning environment have a positive and significant effect on learning achievement from both partial and simultaneous.